2018
DOI: 10.1007/s00256-018-2915-7
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous bilateral lipoma arborescens of bicipitoradial bursa—a rare entity

Abstract: Lipoma arborescens is a rare non-neoplastic condition that affects the synovial lining of joints and bursae accounting for less than 1% of all lipomatous lesions. Characterized by villous proliferation of the synovium, it is an uncommon cause of intra/periarticular mass presenting as a painless, slowly progressive longstanding swelling, and is sometimes accompanied by intermittent monoarticular effusions. We describe a rare case of bilateral lipoma arborescens in the bicipitoradial bursae in a young male refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…All patients (n ¼ 15) demonstrated joint or bursa effusion (Figs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Nine patients with 12 lesions revealed villous or frond-like lesions with a narrow base (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients (n ¼ 15) demonstrated joint or bursa effusion (Figs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Nine patients with 12 lesions revealed villous or frond-like lesions with a narrow base (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these characteristic manifestations on CT and MRI, especially MRI, a definite diagnosis of lipoma arborescens can be made (18). MRI with fat saturation sequences has a high specificity and can draw relatively accurate conclusions, thus avoiding unnecessary biopsy (1,16,18). The previous studies (19,20) found that the lesions were arborescent, frond-like synovial masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by fatty infiltration of the subsynovial connective tissue. It is usually described in the knee (32,33) but may be observed in the hip (34), shoulder (35), wrist (36), or elbow (37). The disease is monoarticular in most cases but involvement of several joints in the same patient has been described (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is monoarticular in most cases but involvement of several joints in the same patient has been described (36,38,39). Extra-/peri-articular location of LA, especially in bursae, such as in the sub acromial space or prepatellar bursa, has been more exceptionally reported (8,9,36,37,40). In some cases, LA may be associated with osteochondral loose bodies (41).…”
Section: Discussionmentioning
confidence: 99%